2016
DOI: 10.1007/s00216-016-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient method for determination of methylene blue dye in water samples based on a combined dispersive solid phase and cloud point extraction using Cu(OH)2 nanoflakes: central composite design optimization

Abstract: A new method was developed for the efficient spectrophotometric determination of methylene blue (MB) dye in solutions. The method is based on a combined dispersive solid phase and cloud point extraction using Cu(OH) nanoflakes (as an adsorbent). Cu(OH) nanoflakes were synthesized by facile and fast methods and characterized using various techniques. The developed method is based on the adsorption of MB on the Cu(OH) nanoflakes and transfer into a surfactant-rich phase using Triton X-114 as a nonionic surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Figure is depicted according to the association between the normal probability (%) and the internally studentized residuals. Its linearity revealed that response transformation was not required and no problem appeared with normality . Therefore, the removal efficiency is reliable.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure is depicted according to the association between the normal probability (%) and the internally studentized residuals. Its linearity revealed that response transformation was not required and no problem appeared with normality . Therefore, the removal efficiency is reliable.…”
Section: Resultsmentioning
confidence: 92%
“…ANOVA is able to determine what measure change of a certain factor causes a significant difference between the mean values acquired. In addition, it surveys the sufficiency of the regression model (R 2 ) regarding lack of fit test (non‐modeled variation) in response . The results presented in Table achieved from CCD were appraised by ANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…Figure depicts the association between the normal probability (%) and the internally studentized residuals. Its linearity reveals that response transformation is not required and no problem appeared with normality . Therefore, the removal efficiency is reliable.…”
Section: Resultsmentioning
confidence: 93%
“…Its linearity reveals that response transformation is not required and no problem appeared with normality. [37] Therefore, the removal efficiency is reliable. Adequate precision equals the ratio of the signal to noise.…”
Section: Rsm Optimization Via Central Composite Designmentioning
confidence: 99%
“…Therefore, the removal of dyes from wastewater to avoid severe toxicity to aquatic life is one of the most pressing scientific concerns. So far, several techniques have been employed to combat this issue, including nanofiltration [ 3 ], cloud point extraction [ 4 ], ozonation [ 5 ], flocculation [ 6 ], photo-degradation [ 7 ], oxidation [ 8 ], coagulation [ 9 ], and microbial degradation [ 10 ]. However, various inadequacies, such as high operational costs, inefficiency, and generation of toxic byproducts, hinder the applicability of these techniques for wastewater treatment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%